A faunistic review of ground beetles of Lebiinae Bonelli, 1810 (Coleoptera: Carabidae) of Lithuania - Tamutis, Vytautas; Barševskis, Arvids (Entomologica Fennica, 2014)
The paper presents the first review on species composition and distribution of ground beetles of Lebiinae Bonelli, 1810, subfamily (Coleoptera: Carabidae) in Lithuania. During the study, all available related published sources have been reviewed. A total of 482 records have been analyzed and more than 700 specimens collected since 1923 have been examined. Lebiinae subfamily is presented by 2 tribes in Lithuania. The tribe Odocanthini is monotypical with a single species. The other one, Lebiini tribe, is more diverse, represented by 4 subtribes, 7 genera and 24 species. The information on distribution, frequency and some features of ecology and zoogeography of 25 Lebiinae species found in Lithuanian is detailed. Demetrias atricapillus (Linnaeus, 1758) is reported for the first time for Lithuanian fauna and Philorhizus notatus (Stephens, 1827) is removed from the list of Lithuanian beetles.